2020
DOI: 10.1007/s00190-020-01381-9
|View full text |Cite
|
Sign up to set email alerts
|

Geodetic VLBI for precise orbit determination of Earth satellites: a simulation study

Abstract: Recent efforts of tracking low Earth orbit and medium Earth orbit (MEO) satellites using geodetic very long baseline interferometry (VLBI) raise questions on the potential of this novel observation concept for space geodesy. Therefore, we carry out extensive Monte Carlo simulations in order to investigate the feasibility of geodetic VLBI for precise orbit determination (POD) of MEO satellites and assess the impact of quality and quantity of satellite observations on the derived geodetic parameters. The MEO sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…VLBI can currently be connected to the satellite techniques only via the station network and the local ties, and is not able to contribute to the geocenter determination. However, numerical simulations demonstrated that geodetic VLBI is able to observe geocenter motion using observations of Galileo satellites (Klopotek et al 2020), suggesting that the GENESIS mission will enable a VLBI-contribution to the estimation of geocenter motion.…”
Section: Improvements In the Itrf Geocenter And Scalementioning
confidence: 99%
See 2 more Smart Citations
“…VLBI can currently be connected to the satellite techniques only via the station network and the local ties, and is not able to contribute to the geocenter determination. However, numerical simulations demonstrated that geodetic VLBI is able to observe geocenter motion using observations of Galileo satellites (Klopotek et al 2020), suggesting that the GENESIS mission will enable a VLBI-contribution to the estimation of geocenter motion.…”
Section: Improvements In the Itrf Geocenter And Scalementioning
confidence: 99%
“…In summary, to strengthen the link between VLBI and the satellite techniques, it is imperative to use improved and better ties than what is currently available, i.e., the local ties at the relatively few VLBI/GNSS co-located sites. Initial work with dedicated space tie satellites demonstrated the feasibility of this approach, see simulations by Anderson et al (2018) or Klopotek et al (2020) and real observations to the APOD-A satellite by Hellerschmied et al (2018). Dedicated VLBI beacons transmitting at VLBI frequencies on a well-calibrated satellite such as GENESIS will enable the observation of satellites with VLBI radio telescopes.…”
Section: Unification Of Reference Frames and Earth Rotationmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies raise the subject of possible co‐location in space for different space techniques. However, most of them are based on simulated data, yet they indicate the advantage of the space ties over the inter‐technique linkage on the ground (Anderson et al., 2018; Glaser et al., 2019; Klopotek et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies raise the subject of possible co-location in space for different space techniques. However, most of them are based on simulated data, yet they indicate the advantage of the space ties over the inter-technique linkage on the ground (Anderson et al, 2018;Glaser et al, 2019;Klopotek et al, 2020). Thaller et al (2011) conducted the co-location onboard navigation satellites using SLR observations to GLONASS and the only pair of GPS satellites equipped with LRAs.…”
mentioning
confidence: 99%